Library disasters preparedness of librarians in selected public and academic libraries - Ramirez, Maria Katrin C. (2011)
This study gathered information on the library disaster preparedness of four (4) prestigious public and academic libraries, namely: the Quezon City Public Library, the Marikina City Public Library, the Ateneo de Manila University Rizal Library, and the University of the Philippines Main Library.